Comparison of green tea and probiotic as alternatives to antibiotic growth promoter in broiler ration (Bangladesh Veterinarian, 2019)
Feed supplements were used up to 35 days in 240 Cobb-500 broilers divided randomly into four groups. The treatments were: control (basal diet; no additives), antibiotic (basal diet + antibiotic), probiotic (basal diet + protexin) and green tea (basal diet + 0.25% green tea powder). Body weight and body weight gain increased significantly (P